Synthesis, Labeling and Preclinical Evaluation of a Squaric Acid Containing PSMA Inhibitor Labeled with 68Ga: A Comparison with PSMA‐11 and PSMA‐617. (19th March 2020) - Greifenstein, Lukas; Engelbogen, Nils; Lahnif, Hanane; Sinnes, Jean‐Philippe; Bergmann, Ralf; Bachmann, Michael; Rösch, Frank
Abstract: The L‐lysine urea‐L‐glutamate (KuE) represents a key motif in recent diagnostic and therapeutic radiopharmaceuticals targeting the prostate specific membrane antigen (PSMA). Using a squaric acid moiety for coupling of KuE with a radioactive label, the squaric acid as a linker in the PSMA ligand seems to mimic the aromatic structure of the naphthylalanine unit on PSMA‐617. In this work, we investigate the influence of squaric acid moiety on the biological activity of the compound carrying a KuE motif and three typical chelates. The derivatives TRAM.SA.KuE, DOTAGA.SA.KuE and NODAGA.SA.KuE were all synthesized in straightforward organic reactions and purified by HPLC afterward. Different amounts of tracer were labeled at different temperatures with 68 Ga. PET examinations were performed on NMRInu/nu nude mice with an LNCaP tumor on the right hind leg including ex vivo investigations of the organs. For comparison, 68 Ga‐derivatives of PSMA‐11 and PSMA‐617, the derivatives most commonly used in clinics, were investigated in the same animal model. Abstract : It′s hip to be squaric : A new class of PSMA inhibitors using squaric acid mediated coupling has been synthesized and labeled with 68 Ga (red). Initial preclinical trials have shown that these compounds, despite their simplified structure, show similar uptake into LNCaP tumor cells as [ 68 Ga]Ga‐PSMA‐11 and [ 68 Ga]Ga‐PSMA‐617 (green) and also a drastically reduced kidney accumulation.